The Usability of Blood Glucose Meters: Task Performance Differences Between Younger and Older Age Groups. (September 2017) - Jones, Jessica; Caird, Jeff K.
This study examines the overall usability of current, commercially available self-monitoring blood glucose (SMBG) meters in order to highlight how the design affects the performance of younger and older adults. Sixteen younger participants (18-27) and 29 elderly participants (65-85) attempted to complete two tasks: 1) set date/time and 2) perform a control solution test, using two meters: the Accu-Check Compact Plus® and 2) the One Touch Ultra 2®. Overall, elderly participants had significantly more difficulty completing the two tasks and committed significantly more errors than younger participants. When using the Accu-Chek® meter to set the date and time 79% of elderly adults failed compared to 12% of younger adults. When using the One Touch® meter, 21% of elderly adults failed to complete the task while none of the younger adults failed. Across the two tasks, elderly participants made, on average, an additional 1.6 errors compared to those in the younger group.